Dinamika Seksualitas dan Represi Perselingkuhan: Analisis Freudian dalam Film Ipar Adalah Maut - Nensilianti Nensilianti; Ridwan Ridwan; Nurul Aini (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study analyzes the psychoanalytic dynamics of infidelity in the film Ipar Adalah Maut using a qualitative approach and textual analysis based on Freudian theory. This research addresses the limited scholarly attention to the interplay of the Id, Ego, and Superego within the Indonesian cultural context, where strong religious and moral norms generate a distinct pattern of sexual conflict compared to Western representations. Data consisting of dialogues, gestures, visual symbols, and cinematic scenes were collected through repeated observations and examined using a psychoanalytic content analysis framework that emphasizes the dynamics of libido, repression, and ego defence mechanisms. The findings indicate that libido is triggered by a simple visual stimulus and gradually intensifies through repeated physical proximity, whereas trauma and transference reinforce the characters’ pathological attachment. The Ego subsequently transforms into a facilitator of destructive impulses through rationalization, denial, and secondary revision, leading the sexual relationship to develop into compulsive and manipulative behavior. The climax is marked by parapraxis and the return of the repressed, which exposes hidden deceit and dismantles the characters’ moral and relational structures. This study contributes to Indonesian film psychoanalysis by demonstrating how culture, trauma, and repetition shape destructive erotic dynamics in cinematic narratives.